Methods for effective teaching meeting the needs of all students - Burden, Paul R.; Byrd, David M. (Hoboken, NJ Pearson Education, Inc, 2025)
"The Methods for Effective Teaching provides research-based coverage of general teaching methods while emphasizing contemporary topics such as culturally responsive teaching, differentiated instruction, and data-driven decision making"-- Provided by publisher.
Includes bibliographical references (pages 429-450) and index.
Keywords: Effective teaching; Teaching